Acute myocarditis morphologically mimicking reverse takotsubo cardiomyopathy - Sherief Sulaiman; Gopalan Nair Rajesh; Haridasan Vellani (IHJ Cardiovascular Case Reports, 2017)
We report a case of acute myocarditis in a middle aged woman in which the left ventricle morphologically mimics reverse takotsubo cardiomyopathy. The two conditions typically mimic acute coronary syndrome and have to be differentiated early. Our case emphasizes the importance of multimodal cardiac evaluation in suspected cases to achieve a correct diagnosis.